Distinct Permafrost Conditions Across the Last Two Glacial Periods in Midlatitude North America. Issue 22 (20th November 2019) - Batchelor, Cameron J.; Orland, Ian J.; Marcott, Shaun A.; Slaughter, Richard; Edwards, R. Lawrence; Zhang, Pu; Li, Xianglei; Cheng, Hai
Abstract: During past glacial periods, extensive areas of North America were covered by permafrost. The timing and extent of these paleo‐permafrost conditions, however, remains ambiguous. Here we present a 250, 000‐year record of speleothem growth from a midlatitude North American cave and report 141 U‐Th ages with hiatuses in growth that reflect the development of temporally continuous permafrost. Combined with U‐Th ages from other speleothem studies, we demonstrate that regional permafrost conditions occurred during both of the prior two glacial maxima but were markedly shorter in duration during the penultimate (Marine Isotope Stage 6, MIS 6) versus the last (MIS 2) glacial period. Notably, a network of sea surface temperatures indicates that mid‐ and low‐latitude temperatures were 0.9 °C ± 0.2 °C warmer during the culmination of MIS 6 versus MIS 2. Our results illustrate the importance of developing regional paleo‐permafrost records and highlight the sensitivity of permafrost conditions during glacial periods to relatively small differences in global‐scale temperature. Plain Language Summary: Permafrost is an important reservoir of carbon during glacial periods. Our understanding of the timing and spatial extent of permafrost conditions during recent glaciations, however, is lacking because of a paucity of paleo‐permafrost indicators. Here we present a new, high‐precision chronology of speleothem growth in a Wisconsin (USA) cave that constrains permafrost conditions during the last two glacial periods. The new record suggests that permafrost conditions endured for 18 ka during the culmination of the last glacial period but were ephemeral during the penultimate glacial period. Our findings are supported by sea surface temperature reconstructions that indicate the penultimate glaciation was nearly 1 °C warmer than the last glacial period. These results provide useful information for quantifying the sensitivity of permafrost to past temperature changes. Key Points: A 250, 000‐year record of speleothem growth from Wisconsin (USA) reveals differing permafrost persistence in the last two glacial periods Paleo‐permafrost indicators across the American Midwest suggest that the penultimate glaciation was warmer than the last glacial period A network of midlatitude and tropical sea surface temperatures demonstrates a 1 °C difference between the last two glacial periods